2023
DOI: 10.1039/d3ce00571b
|View full text |Cite
|
Sign up to set email alerts
|

A highly thermal and pH-stable fluorescence sensor for rapid detection of Hg2+, Fe3+, and tetracycline in aqueous solutions

Abstract: Under solvothermal conditions, one new CdⅡ coordination polymer [Cd(bbimc)(ata)]n (1)] based on carbazole ligand 3,6-bis (1H-benzo[d]imidazol-1-yl)-9-methyl-9H-carbazole (bbimc) and 2-aminoterephthalic acid ligand (H2ata) was synthesized. Single-crystal structural determination reveals that 1...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…33 Similarly, Sun et al, the group reported carbazole-based rigid ligand toward fluorescence sensor for rapid detection of Hg 2+ , Fe 3+ , and tetracycline in aqueous solutions. 34 Advancements in the application of coordination polymers (CPs), which are hybrid organic/inorganic porous materials, are being made in the sensory detection field. 35 Due to various parameters like unique topology, conformational rigidity, structural tunability, and intrinsic cavity voids, CPs exhibit great selectivity toward certain analytes based on their size, shape, and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…33 Similarly, Sun et al, the group reported carbazole-based rigid ligand toward fluorescence sensor for rapid detection of Hg 2+ , Fe 3+ , and tetracycline in aqueous solutions. 34 Advancements in the application of coordination polymers (CPs), which are hybrid organic/inorganic porous materials, are being made in the sensory detection field. 35 Due to various parameters like unique topology, conformational rigidity, structural tunability, and intrinsic cavity voids, CPs exhibit great selectivity toward certain analytes based on their size, shape, and functionality.…”
Section: Introductionmentioning
confidence: 99%